2018
DOI: 10.1158/0008-5472.can-18-0043
|View full text |Cite
|
Sign up to set email alerts
|

SMAD4 Suppresses WNT-Driven Dedifferentiation and Oncogenesis in the Differentiated Gut Epithelium

Abstract: The cell of origin of colon cancer is typically thought to be the resident somatic stem cells, which are immortal and escape the continual cellular turnover characteristic of the intestinal epithelium. However, recent studies have identified certain conditions in which differentiated cells can acquire stem-like properties and give rise to tumors. Defining the origins of tumors will inform cancer prevention efforts as well as cancer therapies, as cancers with distinct origins often respond differently to treatm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 41 publications
3
49
0
Order By: Relevance
“…CTNNB1 (also known as β-catenin), for instance, is induced by SMAD4 in human Tenon's capsule fibroblasts; this factor is involved in the promotion of cell proliferation and activation by TGF-β signaling pathways 9 . Conversely, nuclear β-catenin and other signature genes of the Wnt signaling pathway are upregulated in epithelial tumors harboring Smad4-KO 49 . However, the mechanism by which SMAD4 directly regulates the components of the Wnt signaling pathway had been unclear.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CTNNB1 (also known as β-catenin), for instance, is induced by SMAD4 in human Tenon's capsule fibroblasts; this factor is involved in the promotion of cell proliferation and activation by TGF-β signaling pathways 9 . Conversely, nuclear β-catenin and other signature genes of the Wnt signaling pathway are upregulated in epithelial tumors harboring Smad4-KO 49 . However, the mechanism by which SMAD4 directly regulates the components of the Wnt signaling pathway had been unclear.…”
Section: Discussionmentioning
confidence: 98%
“…The TGF-β signaling pathway is multifunctional, and controls many biological functions related to development and diseases, usually via interactions with other important signaling pathways such as BMP, ERK, Hippo, JAK/STAT, Notch, NF-κB, MAPK, and Wnt signaling pathways 9,47,48 . In particular, crosstalk between the TGF-β and Wnt signaling pathways has been extensively studied 49,50 . However, the regulatory relationship between these pathways in mammalian ovaries, and the specific mechanism involved in their interactions, remain largely unknown 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that blocking BMP signalling leads to the formation of ectopic crypt and epithelial hyperplasia in transgenic mice, with histology resembling human Juvenile Polyposis commonly caused by BMPR1A or SMAD4 mutations 41 42. More recently, two transgenic mouse models demonstrated that inhibition of the BMP pathway by GREM1 hyperexpression (a BMP inhibitor)43 or SMAD4 inactivation44 can resensitise mature villus cells to form ectopic crypts, and concurrent activation of Wnt signalling has a synergistic effect in initiating neoplasia. A recent study has attempted to re-create the traditional serrated adenoma from normal human colon organoids through CRISPR-Cas9 chromosome engineering of R-spondin fusion, TP53 mutation and BRAF mutation 22.…”
Section: Discussionmentioning
confidence: 99%
“…Both populations have been linked to cancer generation in mouse models ( 24 , 26 , 27 ). In colon cancers, recent studies in mice have shown that even differentiated intestinal epithelial cells can be potential CSCs ( 28 ). The fact that adult differentiated cells, tissue resident stem cells or their progeny can promote tumor generation has also been shown in the liver.…”
Section: Cscs and Their Origin At Tumor Initiationmentioning
confidence: 99%